Peningkatan Produksi Kakao melalui Penerapan Teknologi Kakao Sehat pada Kelompok Tani ”Wonga Mengi” di Desa Kedebodu, Kecamatan Ende Selatan, Kabupaten Ende, Propinsi Nusa Tenggara Timur - Sri Wahyuni; Josina I.B Hutubessy; Ferdinandus Lidang Witi (PRIMA: Journal of Community Empowering and Services, 2019)
Title: Increasing of Cocoa Production through the Application of Healthy Cocoa Technology in the "Wonga Mengi" Farmer Group in Kedebodu Village, South-Ende District, Ende Regency, East Nusa Tenggara Province. Kedebodu Village is located 12 km from the capital city of Ende Regency, which is part of the population earning a living as a cocoa farmer. The average land area of cocoa farmers is ± 2 ha/person with average productivity of 140 kg/ha which is very far from the ideal cocoa potential of 1,150 - 2,000 kg/ha. This condition is caused by the age of cocoa plants that are no longer productive, lack of care and high levels of pests and diseases. The service activity aims to increase the knowledge and skills of cocoa farmers in applying healthy cocoa technology so that the production of cocoa plants, especially in the "Wonga Mengi" farmer group in the village of Kedebodu, can be increased. The method used is participatory in the form of field schools by providing material and its application directly in the garden. There are two main program activities, namely providing direct assistance in the form of superior cocoa seedlings in the form of cuttings or entries and pruning tools as well as providing assistance in the application of healthy cocoa technology. After mentoring for about 4 months, it is known that there is an increase in farmers' knowledge about the application of healthy cocoa technology by an average of 72.22% and skills by 67.5%. Until now there has been an increase in fruit volume both in quantity and quality, which is shown by an increase in the number of ovaries/trees (36.68%), the number of fruits/trees (20%), and the dry weight of seeds/trees (30.2%). With this service, an increase in the knowledge and skills of the "Wonga Mengi" farmer group in implementing healthy cocoa technology has an impact on increasing cocoa production.